29.1k views
4 votes
-5(2× - 4)=2(x - 8) with work please :)​

2 Answers

1 vote
Distribute the -5 to 2x and -4 which would be: -10x+20=2(x-8)
Then distribute the 2 to x and -8 which would be: -10x+20=2x-16
Subtract 20 from both sides:-10x+20=2x-16
-20. -20
10x= 2x-36
Subtract 2x from both sides: -10x=2x-36
-2x. -2x
-12x=-36
Divide -12 from both sides: -12x=-36
-12/-12= -36/-12
So in the end x=3
User Lars Blumberg
by
5.4k points
7 votes

Answer:

Explanation:

−5(2)(−4)=2(x−8)

Simplify both sides of the equation.

−5(2)(−4)=2(x−8)

−5(2)(−4)=(2)(x)+(2)(−8)(Distribute)

40=2x+−16

40=2x−16

Step 2: Flip the equation.

2x−16=40

Step 3: Add 16 to both sides.

2x−16+16=40+16

2x=56

Step 4: Divide both sides by 2.

2x/2 = 56/2

x=28

User Ashawn
by
5.0k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.